Slovenian complementary health insurance reform: Dichotomy between the internal market and the social dimension - Bruno Nikolic (DANUBE: Law, Economics and Social Issues Review, 2015)
Complementary health insurance is divided between the internal market (market principles) and social dimension, wherein the state has an extremely difficult task, as it must create the conditions necessary for the fair and efficient functioning of the health care financing system. Slovenia has failed to successfully accomplish this task, which consists of both ensuring the social dimension and also facilitating the operation of market principles. The aim of this article is not on the functioning of market principles, which are covered by the field of economics, but is instead on analyzing the dichotomy between the internal market (the rules that govern the functioning of the internal market) and the social dimension (the rules that enable the exercise of the social function), and, in this light, analyzes the legal regulation of the Slovenian complementary health insurance. Analysis of the legal regulation highlights the shortcomings in ensuring the social dimension, shortcomings which are, with the help of the measures proposed in the concluding section of the article, remedied by the author.
Keywords: 330; Complementary Health Insurance; Internal Market; Social Dimension; Earmarked Taxation